Phthalonitrile monomers and curable compositions containing phthalonitrile monomers
Patent Information
- Application Number
- JP2026518527
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-29
- Filing Date
- 2024-07-22
- Publication Date
- 2026-10-13
Smart Images

Figure 2026533880000001_ABST
Abstract
Description
[Technical Field]
[0001] This disclosure relates to a phthalonitrile monomer and a curable composition for inkjet adaptive planarization (IAP) comprising the phthalonitrile monomer, wherein the curable composition is adapted to form a cured layer having high thermal stability. [Background technology]
[0002] Inkjet adaptive planarization (IAP) is a process that planarizes a substrate surface by spraying droplets of a photocurable composition onto the substrate surface (e.g., a wafer containing electrical circuits) and directly contacting the added liquid with a flat top layer to form a flat liquid layer. This flat liquid layer is typically solidified by exposure to ultraviolet light or heat, and after removal of the top layer, a flat polymer surface is obtained. This surface can then be subjected to subsequent processing steps, such as baking, etching, and / or further deposition steps.
[0003] The subsequent baking of the formed cured layer is often carried out at temperatures that can reach 350°C, 400°C, or even 450°C, requiring the photocured layer to have high thermal stability and low shrinkage. Most current UV-curable resists are acrylate-based resists that begin to degrade below 300°C.
[0004] There is a need for improved IAP materials that have a long shelf life and can form a flat cured layer with high thermal stability in subsequent processing. [Overview of the project]
[0005] In one embodiment, the phthalonitrile monomer is of formula (1):(R2) n -X-(R1) m (1) (wherein X is a substituted or unsubstituted aryl(Ar) or arylalkyl group; R1 is [ka] It can have the structure (where R2 is -CH=CH2, n is 1 to 4, and m is 1 to 4).
[0006] In one embodiment, X in formula (1) of the phthalonitrile monomer may include benzyl, biphenyl, Ar1-O-Ar2, or Ar1-CH2-Ar2.
[0007] In certain embodiments, the monomer is of formula (2), (3), or (4): [ka] It can include structures selected from.
[0008] In another embodiment, the curable composition may include a polymerizable material, where the polymerizable material is given by formula (1):(R2) n -X-(R1) m (1) (wherein X is a substituted or unsubstituted aryl or arylalkyl; R1 is [ka] It can contain phthalonitrile monomers having the structure (where R2 is -CH=CH2; n is 1 to 4; and m is 1 to 4).
[0009] In one embodiment of the curable composition, X in formula (1) of the phthalonitrile monomer may include benzyl, biphenyl, diphenyl ether, Ar1-O-Ar2, or Ar1-CH2-Ar2.
[0010] In a further embodiment, the phthalonitrile monomer of the curable composition is of formula (2), (3), or (4): [ka] It can have a structure selected from the following.
[0011] In one embodiment of the curable composition, the amount of the phthalonitrile monomer of formula (1) may be at least 1 wt% and up to 40 wt% relative to the total weight of the polymerizable material. In a particular aspect, the amount of the phthalonitrile monomer may be at least 5 wt% and up to 20 wt% relative to the total weight of the polymerizable material.
[0012] In another embodiment of the curable composition, the polymerizable material can comprise at least one second monomer that does not contain a phthalonitrile group.
[0013] In one aspect, the at least one second monomer of the curable composition can comprise an aromatic polyfunctional vinyl monomer. In a particular aspect, the second monomer can comprise a divinylbenzene monomer, a trivinylbenzene monomer, a divinyldiphenyl monomer, a trivinyldiphenyl monomer, a tetravinyldiphenyl monomer, a divinyldiphenyl ether monomer, a trivinyldiphenyl ether monomer, a tetravinyldiphenyl ether monomer, a divinyldiphenylmethane monomer, a trivinyldiphenylmethane monomer, a tetravinyldiphenylmethane monomer, or any combination thereof.
[0014] In another aspect of the curable composition, the amount of the aromatic polyfunctional vinyl monomer of the second monomer may be at least 50 wt% relative to the total weight of the polymerizable material.
[0015] In one embodiment, the viscosity of the curable composition, when measured according to the Brookfield method, may be 30 mPa·s or less at 23°C.
[0016] In another embodiment of the curable composition, the amount of the polymerizable material may be at least 90 mass% relative to the total mass of the curable composition.
[0017] In one aspect of the curable composition, the polymerizable material can have a carbon content of at least 80 percent relative to the total molecular weight of the polymerizable material.
[0018] In another embodiment, the laminate may comprise a substrate and a cured layer covering the substrate, the cured layer of which may be formed from the curable composition.
[0019] In one embodiment of the laminate, the initial thermal decomposition temperature T(X) of the cured layer may be at least 400°C.
[0020] In a further embodiment, a method for forming a cured layer on a substrate is to apply a layer of a curable composition to the substrate, wherein the curable composition comprises a polymerizable material and an initiator, and the polymerizable material is of formula (1):(R2) n -X-(R1) m (1) (wherein X is a substituted or unsubstituted aryl or arylalkyl, and R1 is [ka] The process may include: applying a layer of a curable composition containing a phthalonitrile monomer having the structure (where R2 is -CH=CH2, n is 1 to 4, and m is 1 to 4) onto a substrate; contacting the curable composition with an imprint template or top layer material; polymerizing the curable composition by light or heat to form a cured layer; and removing the imprint template or top layer material from the cured layer.
[0021] In one embodiment of the method, the initial thermal decomposition temperature T(X) of the cured layer may be at least 400°C.
[0022] In further embodiments, a method for manufacturing an article may include forming a cured layer on a substrate; forming a pattern on the substrate; processing the substrate on which the pattern is formed; and manufacturing an article from the substrate processed in the processing, in accordance with the method for forming a cured layer described above.
[0023] The embodiments are illustrated illustratively and are not limited to the attached drawings. [Brief explanation of the drawing]
[0024] [Figure 1] This graph shows the TGA curves obtained by dynamic thermogravimetric analysis for a cured layer sample formed from a curable composition S1 according to one embodiment, and for the cured layer of a comparative sample C1. [Figure 2] This graph shows the TGA curves obtained by isothermal thermogravimetric analysis at 350°C and 400°C for a cured layer sample formed from a curable composition S1 according to one embodiment, and for the cured layer of a comparative sample C1. [Modes for carrying out the invention]
[0025] The following description is provided to aid in understanding the teachings disclosed herein and focuses on specific implementations and embodiments of the teachings. This focus is provided to aid in the explanation of the teachings and should not be construed as a limitation on the scope or applicability of the teachings.
[0026] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present invention pertains. Materials, methods, and examples are illustrative for illustrative purposes only and are not intended to limit the scope of the invention. Much of the detail relating to specific materials and processes not described herein is prior art and can be found in textbooks and other sources in the field of printing and lithography.
[0027] As used herein, “comprises,” “comprising,” “includes,” “including,” “has,” “having,” or variations thereof are intended to cover non-exclusive inclusion. For example, a process, method, article, or apparatus that includes a list of features is not necessarily limited to those features alone and may include other features not expressly described or that are inherent to such process, method, article, or apparatus.
[0028] Where used herein, unless expressly stated otherwise, “or” means an inclusive, not exclusive, “or.” For example, if condition A or B is met, then one of the following is true: A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), or both A and B are true (or exist).
[0029] Furthermore, the denominators "a" or "an" are used to describe elements and components described herein. This is done solely for convenience and to illustrate the general concept of the scope of the invention. Such descriptions should be interpreted as including one or at least one, and unless otherwise clearly intended, singular forms also include plural forms.
[0030] In one embodiment, the present disclosure relates to formula (1):(R2) n -X-(R1) m (1) (wherein X is a substituted or unsubstituted aryl or arylalkyl; R1 is [ka] This relates to a phthalonitrile monomer having the structure (where R2 is -CH=CH2; n is 1 to 4; and m is 1 to 4). R2 can be located at any position on the aryl or arylalkyl group X.
[0031] In one embodiment, X in formula (1) may include benzyl, biphenyl, Ar1-O-Ar2, or Ar1-CH2-Ar2. In a particular embodiment, Ar1-O-Ar2 may be a biphenyl ether. In another embodiment, Ar1-CH2-Ar2 may be biphenylmethane. In a particular embodiment, R2 may include at least two vinyl groups. These vinyl groups may be present in either Ar1 or Ar2. Alternatively, two or more vinyl groups of R2 may be present in both Ar1 and Ar2.
[0032] Non-limiting examples of the phthalonitrile monomer of formula (1) include the structures of formulas (2), (3), or (4). [ka]
[0033] The disclosure further relates to a curable composition comprising a polymerizable material and an initiator, wherein the polymerizable material may include a phthalonitrile monomer. In one embodiment, the phthalonitrile monomer of the curable composition may have the structure of the phthalonitrile monomer of formula (1) above.
[0034] Surprisingly, it has been observed that curable compositions containing the phthalonitrile monomer of formula (1) in specific combinations with one or more other polymerizable monomers can exhibit very high thermal stability.
[0035] As used herein, the phrase "one or more other polymerizable monomers" is synonymous with "at least one secondary monomer," wherein the at least one secondary monomer does not contain a phthalonitrile group.
[0036] In one embodiment, the amount of phthalonitrile monomer of formula (1) may be at least 1% by weight, or at least 3% by weight, or at least 5% by weight, or at least 7% by weight, or at least 10% by weight, or at least 15% by weight, or at least 20% by weight, relative to the total weight of the polymerizable material. In another embodiment, the amount of phthalonitrile monomer may be 40% by weight or less, or 35% by weight or less, or 30% by weight or less, or 25% by weight or less, or 20% by weight or less, or 12% by weight or less, or 10% by weight or less, relative to the total weight of the polymerizable material. In a particular embodiment, the amount of phthalonitrile monomer may be at least 5% by weight and 20% by weight or less, relative to the total weight of the polymerizable material.
[0037] In one embodiment, at least one second monomer may include at least one aromatic polyfunctional vinyl monomer. As used herein, the term aromatic polyfunctional vinyl monomer relates to a polymerizable monomer comprising at least one aromatic ring structure and at least two vinyl groups.
[0038] In some embodiments, the second monomer may include vinylbenzene monomer, divinylbenzene monomer, trivinylbenzene monomer, divinyldiphenyl monomer, trivinyldiphenyl monomer, tetravinyldiphenyl monomer, divinyldiphenyl ether monomer, trivinyldiphenyl ether monomer, tetravinyldiphenyl ether monomer, divinyldiphenylmethane monomer, trivinyldiphenylmethane monomer, tetravinyldiphenylmethane monomer, or any combination thereof. The polyfunctional vinylbenzene monomer may further be substituted with alkyl groups or other functional groups, such as halogens, amines, hydroxyl groups, or carboxyl groups.
[0039] Non-limiting examples of the structures of aromatic polyfunctional vinyl monomers are: [ka] ; or any combination thereof.
[0040] The amount of at least one aromatic polyfunctional vinyl monomer of at least one second monomer may be at least 50% by weight, or at least 65% by weight, or at least 70% by weight, or at least 75% by weight, or at least 80% by weight, or at least 85% by weight, or at least 90% by weight, or at least 95% by weight, based on the total weight of the polymerizable material. In another embodiment, the amount of at least one aromatic polyfunctional vinyl monomer may be 99% by weight or less, or 95% by weight or less, or 90% by weight or less, or 88% by weight or less, or 85% by weight or less, or 80% by weight or less, or 75% by weight or less, or 70% by weight or less, or 65% by weight or less, or 60% by weight or less, based on the total weight of the polymerizable material. In a particular embodiment, the amount of at least one aromatic polyfunctional vinyl monomer of the second monomer may be at least 80% by weight and 95% by weight or less, based on the total weight of the polymerizable material.
[0041] In certain embodiments, the carbon content of the aromatic polyfunctional vinyl monomer of at least one second monomer may be at least 86%, or at least 88%, or at least 90%, or at least 91%, or at least 92%, or at least 93% of the total molecular weight of the aromatic polyfunctional vinyl monomer.
[0042] In certain embodiments, at least one second monomer may essentially consist of at least one aromatic polyfunctional vinyl monomer. As used herein, at least one second monomer essentially consisting of an aromatic polyfunctional vinyl monomer means that the polymerizable material contains at least one phthalonitrile monomer of formula (1) and at least one second monomer, wherein 99% by weight of the at least one second monomer is at least one aromatic polyfunctional vinyl monomer.
[0043] In a further embodiment, the weight percentage ratio of the phthalonitrile monomer to the aromatic polyfunctional vinyl monomer in the second monomer may be 1:2 to 1:20, for example, 1:3 to 1:15, or 1:4 to 1:12, or 1:5 to 1:10.
[0044] The inclusion of a large amount of aromatic polyfunctional vinyl monomer as at least one secondary monomer, along with the phthalonitrile monomer of formula (1), offers the advantage of a higher carbon content in the polymerizable material, which can contribute to a high final carbon content in the solid layer formed after curing. In certain embodiments, the carbon content of the polymerizable material may be at least 72%, or at least 74%, or at least 76%, or at least 78%, or at least 80%, or at least 82%, or at least 84%, or at least 86%, at least 88%, or at least 90% of the total molecular weight of the polymerizable material. Assuming that all of the polymerizable material cures to form a solid layer, the carbon content of the solid layer formed after curing of the curable composition may be approximately equal to the carbon content of the polymerizable material.
[0045] In another embodiment, the polymerizable material of the curable composition may include a certain amount of polymerizable monomers, oligomers, or polymers in addition to the phthalonitrile monomer and at least one aromatic polyfunctional vinyl monomer. Non-limiting examples of such polymerizable monomers include, for example, monofunctional or polyfunctional acrylate monomers or maleimide monomers.
[0046] The amount of polymerizable material in the curable composition may be at least 75% by weight, for example, at least 80% by weight, at least 85% by weight, at least 90% by weight, or at least 95% by weight, or at least 97% by weight, relative to the total weight of the photocurable composition. In another embodiment, the amount of polymerizable material may be 99.5% by weight or less, or 99% by weight or less, or 98% by weight or less, or 97% by weight or less, or 95% by weight or less, relative to the total weight of the curable composition. The amount of polymerizable material may be a value between any of the minimum and maximum values shown above. In a particular embodiment, the amount of polymerizable material may be at least 85% by weight and 99% by weight or less.
[0047] A key aspect of monomer selection is maintaining the low viscosity of the polymerizable composition before curing. In one embodiment, the viscosity of the curable composition may be 30 mPa·s or less, for example, 25 mPa·s or less, 20 mPa·s or less, 15 mPa·s or less, or 10 mPa·s or less. In other specific embodiments, the viscosity may be at least 1 mPa·s, for example, at least 3 mPa·s, for example, at least 5 mPa·s, or at least 8 mPa·s. In a particularly preferred embodiment, the photocurable composition may have a viscosity of 15 mPa·s or less. As used herein, all viscosity values relate to viscosity measured at a temperature of 23°C by the Brookfield method using a Brookfield viscometer.
[0048] The curable compositions of this disclosure may be designed so that the cured layer formed from the curable composition has high thermal stability. In one embodiment, the thermal decomposition onset temperature of the photocured layer may be at least 350°C, or at least 375°C, or at least 400°C, or at least 410°C, or at least 420°C, or at least 425°C, or at least 430°C, or at least 435°C, or at least 440°C, or at least 445°C. In another embodiment, the initial thermal decomposition temperature may be 500°C or less, or 480°C or less, or 460°C or less. As used herein, the thermal decomposition onset temperature is also called the “initial thermal decomposition temperature” T(X), and in the TGA curve, it is the temperature at which a deflection of the curve is first observed from a nearly linear plateau just before the rapid decomposition decrease of the sample begins.
[0049] In certain embodiments, the curable compositions of this disclosure may be essentially solvent-free. As used herein, unless otherwise specified, the term solvent refers to a compound that can dissolve or disperse polymerizable monomers but does not polymerize itself during the curing of the curable composition. "Surfactantly solvent-free" means herein that the amount of solvent is 5% by weight or less of the total weight of the curable composition. In certain embodiments, the amount of solvent may be 3% by weight or less, 2% by weight or less, 1% by weight or less, or the curable composition may be solvent-free except for unavoidable impurities.
[0050] In another embodiment, the curable composition and the disclosure may contain a solvent in an amount greater than 5% by weight relative to the total weight of the curable composition. In a particular embodiment, the amount of solvent may be at least 7% by weight, or at least 10% by weight, or at least 15% by weight, or at least 20% by weight relative to the total weight of the curable composition. In another embodiment, the amount of solvent may be 25% by weight or less, or 20% by weight or less, or 10% by weight or less relative to the total weight of the curable composition.
[0051] In another embodiment, to make the curable composition suitable for IAP treatment, the curable composition of this disclosure may be essentially particle-free, for example, pigment particles. As used herein, “essentially particle-free” means that the curable composition contains 50 or fewer particles with a size of 200 nm or larger per ml.
[0052] In yet another embodiment, the curable composition of the present disclosure may not contain an epoxide group-containing monomer, an epoxy group-containing oligomer, or an acrylamide or polyurethane.
[0053] To initiate curing of the curable composition when exposed to light or heat, the curable composition may contain one or more initiators, such as one or more photopolymerization initiators or thermal initiators. In one embodiment, the amount of one or more initiators may be between 1% and 6% by weight of the total weight of the curable composition.
[0054] In certain embodiments, curing can also be carried out by a combination of photocuring and thermal curing.
[0055] The curable composition may further contain one or more optional additives. Non-limiting examples of optional additives include stabilizers, dispersants, solvents, surfactants, inhibitors, or any combination thereof. In certain embodiments, the amount of one or more surfactants may be 0.2% to 5% by weight relative to the total weight of the curable composition.
[0056] In one embodiment, a photocurable composition can be applied to a substrate to form a cured layer. As used herein, the combination of the substrate and the cured layer on the substrate is referred to as a laminate.
[0057] The inclusion of at least a phthalonitrile monomer of formula (1) and at least one second monomer, which is an aromatic polyfunctional vinyl monomer as a polymerizable material, can contribute to a high carbon content in the resulting photocured layer. In one embodiment, the curable composition can be adapted such that the cured layer formed after curing has a carbon content of at least 70%, or at least 72%, at least 74%, at least 76%, at least 78%, or at least 80%, at least 82%, at least 84%, at least 86%, at least 88%, or at least 90% of the total weight of the cured layer. As used herein, the carbon content of the cured layer can be determined by elemental analysis using standard commercial analytical measurement techniques and relates to the weight percentage of carbon based on the total weight of the cured layer. Assuming no material loss occurs during the curing of the curable composition, the calculated carbon content of the polymerizable material may correspond to the carbon content of the cured layer.
[0058] The disclosure further relates to a method for forming a cured layer. The method may include: applying a layer of the curable composition onto a substrate; bringing the curable composition into contact with a template or top layer material; polymerizing the curable composition by light or heat to form a cured layer; and removing the template or top layer material from the cured layer.
[0059] The substrate and the solidified hardened layer can be subjected to additional processing, such as an etching process, which allows an image corresponding to the pattern of either or both of the solidified layer and / or the pattern layer beneath the solidified layer to be transferred to the substrate. The substrate can further be subjected to known steps and processes for device (article) manufacturing, including, for example, curing, oxidation, layering, deposition, doping, planarization, etching, removal of moldable material, dicing, bonding, and packaging.
[0060] The cured layer can be further used as an interlayer insulating film in semiconductor devices such as LSIs, system LSIs, DRAMs, SDRAMs, RDRAMs, or D-RDRAMs, or as a resist film used in semiconductor manufacturing processes.
[0061] As further demonstrated in the examples, it was surprisingly discovered that in curable compositions, specific combinations of polymerizable monomers containing the phthalonitrile monomer of formula (1) and at least one aromatic polyfunctional vinyl monomer as a second monomer can form a curable layer with properties particularly suitable for IAP treatment, such as high thermal stability and high etching resistance. [Examples]
[0062] The following non-limiting examples illustrate the concepts described herein.
[0063] [Example 1]
[0064] Synthesis of 4-(3,5-divinylphenoxy)phthalonitrile (DVBOPCN).
[0065] In the first step, 15 g of 5-hydroxyisophthalaldehyde and 17.3 g of 4-nitro-1,2-phthalonitrile were dissolved in 250 ml of dimethylformamide (DMF), and 1.4 g of K2CO3 4 was added as a catalyst (see also the chemical reaction scheme below). The reaction was carried out at room temperature (23°C) for 16 hours with stirring, and the resulting intermediate product (IP) was separated in 78% yield by preparative chromatography.
[0066] Subsequently, 18 g of the intermediate product (IP), 106 g of methyltriphenyl-phosphonium bromide (Ph3PMeBr), and 33 g of tert-potassium butyrate (t-BuOx) were dissolved in 250 ml of THF and stirred at 28°C for 30 minutes. The reaction product was purified by preparative chromatography to obtain a white powder of DVBOPCN with a purity of 95% (measured by LC-MS). [ka]
[0067] The measured 1H-NMR spectra obtained from DVBOPCN contained the following signals: δ(ppm) 5.36-5.39(d,2H); 5.77-5.81(d,2H), 6.67-6.74(dd,2H), 7.02, 7.02(s,2H), 7.25-7.36(m,3H), 7.73-7.75(m,1H).
[0068] [Example 2]
[0069] Preparation of curable compositions.
[0070] A curable composition (sample S1) was prepared by mixing 10 parts of the phthalonitrile monomer DVBOPCN prepared in Example 1, 90 parts of 3,3'-divinylbiphenyl (DVBPH), 1 part of the surfactant Capstone FS3100 (manufactured by The Chemours Company), 3 parts of the photopolymerization initiator Irgacure 819 (manufactured by BASF), and 3 parts of the photopolymerization initiator OXE02 (manufactured by BASF). This curable composition had a viscosity of 25 mPa·s at 23°C.
[0071] Furthermore, a comparative curable composition (comparative sample C1) was prepared containing 100% by weight of DVBPH as a polymerizable material, and using the same type and amount of surfactant and photopolymerization initiator. The viscosity of comparative composition C1 was 16.1 mPa·s at 23°C.
[0072] Table 1 shows an overview of compositions S1 and C1.
[0073] [Table 1]
[0074] A second set of photocurable compositions (samples S2 and S3) was prepared. Each set consisted of 10 parts DVBOPCN mixed with 90 parts 3,5,3'-vinyl diphenylmethane (TVPM) (sample S2) or 90 parts DVBA (sample S3), further containing 1 part of surfactant Capstone FS3100 (The Chemours Company), 4 parts of photopolymerization initiator Irgacure 651 (BASF), and 1.5 parts of photopolymerization initiator Omnirad 1316 (IGM Resins). Comparative photocurable compositions C2 and C3 contained the same components but lacked DVBOPCN.
[0075] Table 2 shows an overview of the curable compositions S2, C2 and S3, C3 of the second set.
[0076] [Table 2]
[0077] [Example 3]
[0078] Thermal shrinkage rate of the photocured layer after baking.
[0079] Photocurable layers were prepared from the curable compositions summarized in Tables 1 and 2, and the thermal shrinkage rate was measured after baking the cured layers on a hot plate at 350°C for 2 minutes.
[0080] Each liquid-curable composition was applied to a blank fused silica wafer, and a photocured layer was prepared by photocuring the liquid layer with light at a wavelength of 365 nm. The total irradiation doses were 5 J, 10 J, and 20 J. The test was designed so that the average thickness of the resulting photocured film (before baking) was approximately 100 nm.
[0081] The baking treatment of the photocured film was performed by placing the film on a hot plate at temperatures of 375°C and 400°C for 2 minutes. To calculate the thermal shrinkage rate, the thickness of the film before and after the baking treatment was measured using a JA Woolam Spectroscopic Ellipsometer M-2000 X-210. The linear shrinkage rate (Sb 350 ) was calculated by the following formula. Sb 350 =[(T p -T c ) / T p ×100% Here, T p is the thickness of the photocured film before the baking treatment, and T c is the thickness of the photocured film after baking.
[0082] The results of the thermal shrinkage rate measurement are summarized in Table 2. It can be confirmed that the shrinkage rates after baking of Samples S1, S2, and S3 are lower compared to the respective Comparative Samples C1, C2, and C3, in which the curable composition before curing does not contain a phthalonitrile monomer.
[0083]
Table 3
[0084] [Example 4]
[0085] Thermogravimetric analysis.
[0086] The photocured films of Samples S1 and C1 were prepared in the same manner as the method described in Example 3, except that a total UV irradiation dose of 20 J was used, and the thickness of the cured layer (film) was about 300 microns. To evaluate the thermal stability of these layers, the photocured layers were investigated by thermogravimetric analysis (TGA).
[0087] For the TGA measurement, a LINSEIS STA PT1000 apparatus (Linseis Messgeraete GmbH, Germany) was used. All measurements were performed under nitrogen at a flow rate of 5 liters per hour.
[0088] Dynamic thermogravimetric analysis
[0089] In dynamic TGA measurements, 25–35 mg of the photocured layer was placed in a crucible, and the initial weight was recorded. A reference crucible was used to monitor the weight change of the crucible itself due to temperature changes. The sample was heated at a rate of 20°C / min, and the weight loss of the sample due to the temperature increase was recorded at 1-second intervals. The relative weight change rate was calculated by dividing the weight loss by the initial total weight of the sample.
[0090] Figure 1 shows the dynamic TGA curves of the cured layers of samples S1 and C1. It can be confirmed that the cured layer of sample S1 had superior thermal stability compared to sample C1. The initial thermal decomposition temperature (T(X)) of S1 was 430°C, while the initial thermal decomposition temperature T(X) of C1 was 360°C.
[0091] As used herein, the thermal decomposition temperature refers to the initial decomposition temperature T(X). T(X) is the temperature at which the TGA curve first begins to deflect from its nearly linear plateau shape, observed immediately before a rapid decrease in the sample mass (i.e., decomposition).
[0092] Isothermalgravimetric analysis
[0093] Furthermore, isothermal thermogravimetric analysis (TGA) was performed at constant temperatures of 350°C and 400°C for at least 30 minutes. The measurements were performed using the same TGA apparatus as described above, under nitrogen conditions. In each measurement, 25-35 mg of the photocurable sample was placed in a crucible and the initial weight was recorded. The temperature was rapidly increased to the target test temperature (350°C or 400°C) (within 20 minutes), and the weight loss over 30 minutes after reaching the set temperature was recorded. Figure 2 shows the relative weight loss rates of photocurable samples S1 and C1 over 30 minutes at constant temperatures of 350°C and 400°C. At 350°C, both samples remained stable and no weight loss was observed. At 400°C, weight loss occurred over time, and sample S1 showed a slower weight loss rate than the comparative sample C1.
[0094] [Example 5]
[0095] Investigation of double bond conversion rates.
[0096] Fourier transform infrared spectroscopy (FTIR) was performed on the curable compositions S1 and C1 described in Example 2 to investigate the double bond conversion rate after predetermined curing conditions. The C=C conversion was measured using the C=C bending peak (989 cm²) before and after curing. -1 The decrease of the CH benzene ring vibration peak (713 cm) was measured and used as an internal reference. -1 ) was used. A Thermo Nicolet 6700 FTIR (equipped with a DTGS TEC detector) was used at 4000 cm². -1 ~625cm -1 The FTIR spectrum was recorded.
[0097] For the measurement, 0.3–0.5 μl of the sample was dropped onto an NaCl window (25 mm × 25 mm), and then covered with another NaCl window of the same size. The UV irradiation dose was 10 J / cm². 2 It has a wavelength of 365 nm and a UV light intensity of 100 mW / cm². 2 The following was used: The conversion rate of C=C bonds was 989 cm² between the cured sample (after exposure to curing conditions) and the uncured sample (at the start of measurement, before UV exposure). -1 It was calculated from the peak ratio in [location].
[0098] The photocured sample was subjected to a baking treatment at 350°C for 3 minutes on a hot plate under nitrogen, after which a third IR spectrum was obtained.
[0099] Table 3 shows a summary of the calculated C=C conversion rate (percentage) for samples after UV curing and additional baking at 350°C. UV curing confirmed that approximately 53 percent of C=C double bond conversion occurred in both compositions S1 and C1. Additional baking at 350°C further increased C=C conversion to approximately 86.5% in sample S1 and 87.5% in sample C1.
[0100] [Table 4]
[0101] The detailed descriptions and drawings of the embodiments described herein are intended to provide a general understanding of the structures of various embodiments. This specification and the drawings are not intended to describe all elements and features of apparatus and systems that use the structures or methods described herein in an exhaustive and comprehensive manner. Different embodiments may be provided in combination with a single embodiment. Conversely, various features described in the context of a single embodiment for the sake of brevity may also be provided individually or in any partial combination. Furthermore, references to values indicated by a range include all values within that range. Many other embodiments may become apparent to those skilled in the art only after reading this specification. Other embodiments may be used and derived from this disclosure; that is, structural substitutions, logical substitutions, or other modifications may be made without departing from the scope of the disclosure. Therefore, this disclosure should be considered illustrative, not restrictive.
Claims
1. Equation (1): (R) 2 ) n -X-(R) 1 ) m (1) (In the formula, X is a substituted or unsubstituted aryl (Ar) or arylalkyl group; R 1 teeth 【Chemistry 1】 And; R 2 -CH=CH 2 And; A phthalonitrile monomer having the structure n is 1 to 4; m is 1 to 4.
2. -X- is benzyl, biphenyl, Ar 1 -O-Ar 2 , or Ar 1 -CH 2 -Ar 2 The phthalonitrile monomer according to claim 1, comprising:
3. The monomer is of formula (2), (3), or (4): 【Chemistry 2】 The phthalonitrile monomer according to claim 2, comprising a structure selected from the following.
4. A curable composition comprising a polymerizable material and an initiator, The polymerizable material is of formula (1): (R 2 ) n -X-(R 1 ) m (1) (In the formula, X is a substituted or unsubstituted aryl or arylalkyl; R 1 teeth 【Transformation 3】 And; R 2 -CH=CH 2 And; A curable composition comprising a phthalonitrile monomer having the structure (where n is 1 to 4; m is 1 to 4).
5. -X- is benzyl, biphenyl, diphenyl ether, Ar 1 -O-Ar 2 , or Ar 1 -CH 2 -Ar 2 The curable composition according to claim 4, comprising:
6. The phthalonitrile monomer is of formula (2), (3), or (4): 【Chemistry 4】 The curable composition according to claim 5, comprising a structure selected from the following.
7. The curable composition according to claim 4, wherein the amount of the phthalonitrile monomer is at least 1% by weight and 40% by weight or less with respect to the total weight of the polymerizable material.
8. The curable composition according to claim 8, wherein the amount of the phthalonitrile monomer is at least 5% by weight and 20% by weight or less with respect to the total weight of the polymerizable material.
9. The curable composition according to claim 4, wherein the polymerizable material comprises at least one second monomer that does not contain a phthalonitrile group.
10. The curable composition according to claim 1, wherein the second monomer comprises an aromatic polyfunctional vinyl monomer.
11. The curable composition according to claim 10, wherein the second monomer comprises divinylbenzene monomer, trivinylbenzene monomer, divinyldiphenyl monomer, trivinyldiphenyl monomer, tetravinyldiphenyl monomer, divinyldiphenyl ether monomer, trivinyldiphenyl ether monomer, tetravinyldiphenyl ether monomer, divinyldiphenylmethane monomer, trivinyldiphenylmethane monomer, tetravinyldiphenylmethane monomer, or any combination thereof.
12. The curable composition according to claim 10, wherein the amount of the aromatic polyfunctional vinyl monomer is at least 50% by weight relative to the total weight of the polymerizable material.
13. The curable composition according to claim 4, wherein the viscosity of the curable composition is 30 mPa·s or less at 23°C.
14. The curable composition according to claim 4, wherein the amount of the polymerizable material is at least 90% by weight of the total weight of the curable composition.
15. The curable composition according to claim 4, wherein the carbon content of the polymerizable material is at least 80 percent of the total molecular weight of the polymerizable material.
16. A laminate comprising a substrate and a cured layer covering the substrate, wherein the cured layer is formed from the curable composition described in claim 4.
17. The laminate according to claim 16, wherein the initial thermal decomposition temperature T(X) of the hardened layer is at least 400°C.
18. A method for forming a hardened layer on a substrate, Applying a layer of curable composition onto the substrate, wherein the curable composition comprises a polymerizable material and an initiator, and the polymerizable material is of formula (1): (R 2 ) n -X-(R 1 ) m (1) (wherein X is a substituted or unsubstituted aryl or arylalkyl; R 1 teeth 【Transformation 5】 And; R 2 -CH=CH 2 Applying a layer of the curable composition containing a phthalonitrile monomer having the structure (where n is 1 to 4 and m is 1 to 4) onto the substrate; Bringing the curable composition into contact with an imprint template or top layer material; Polymerizing the curable composition by light or heat to form the cured layer; and A method comprising removing the imprint template or top layer material from the cured layer.
19. The method according to claim 18, wherein the initial thermal decomposition temperature T(X) of the hardened layer is at least 400°C.
20. A method for manufacturing articles, Forming the cured layer on the substrate according to claim 18; Forming a pattern on the substrate; In forming the above, processing the substrate on which the pattern is formed; and A method comprising manufacturing the article from the substrate processed in the aforementioned process.